Risk Factors of Bronchial Asthma in Children Between Age Group Of 5 To 14 Years in A Tertiary Care Centre - Jena, Debi Prasad; Mahar, Jatadhari; Priyadarshini, Lipsa; Behera, Bijaya Ketana; Mishra, Pravakar (Journal of Neonatal Surgery, 2025)
Background: Bronchial asthma is a prevalent chronic respiratory disease in children, with inflammation and hyperresponsiveness of the airways. The aim of this study was to assess a range of epidemiological, clinical, and environmental risk factors involved in pediatric bronchial asthma. Methods: One hundred children aged between 5 and 14 years old with clinically diagnosed bronchial asthma and another 100 age- and sex-matched healthy controls were examined for two years (Dec 2020 – Dec 2022). Extended clinical, hematologic, and environmental investigations were carried out. Results: Asthma was more common in boys (M:F ratio 1.7:1), especially in the age group of 5–7 years. Mean hemoglobin concentration was not altered, but total leukocyte number, eosinophil number, platelet number, and ESR were raised significantly in asthmatics, reflecting chronic airway inflammation. There was a strong genetic component with a threefold increased risk in children with a family history of asthma. Allergic rhinitis proved to be the most important risk factor (8-fold risk) followed by atopic dermatitis and dust environment exposure. Cold temperatures and air conditioner use worsened symptoms, but pollen, mold, animal dander, and smoke exposure were not significant. Low birth weight and bottle feeding were associated with increased asthma risk, but exclusive breastfeeding was protective. Conclusion: This research highlights the multifactorial etiology of childhood asthma, with genetic predisposition, allergic rhinitis, and environmental factors being crucial determinants. Early identification and control of risk factors, breastfeeding promotion, and allergen avoidance are critical measures to curb disease burden.